Communicating embedded systems : software and design : formal methods - Jard, Claude; Roux, Olivier H. (ISTE., 2010)
The increased complexity of embedded systems coupled with quick design cycles to accommodate faster time-to-market requires increased system design productivity that involves both model-based design and tool-supported methodologies. Formal methods are mathematically-based techniques and provide a clean framework in which to express requirements and models of the systems, taking into account discrete, stochastic and continuous (timed or hybrid) parameters with increasingly efficient tools.